2017
DOI: 10.1177/1941738117736056
|View full text |Cite
|
Sign up to set email alerts
|

Sport Sampling Is Associated With Improved Landing Technique in Youth Athletes

Abstract: Background:Sport sampling is recommended to promote fundamental movement skill acquisition and physical activity. In contrast, sport specialization is associated with musculoskeletal injury risk, burnout, and attrition from sport. There is limited evidence to support the influence of sport sampling on neuromuscular control, which is associated with injury risk, in youth athletes.Hypothesis:Athletes who participated in only 1 sport during the previous year would demonstrate higher Landing Error Scoring System (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 40 publications
2
87
0
Order By: Relevance
“…28 Previous authors who evaluated landing patterns on the LESS in a youth athlete population showed that an average total LESS score ,5 was associated with a decreased risk of ACL injury 16 and that athletes who had been exposed to a variety of sport experiences had better movement techniques. 20 Gymnasts in this sample had average total LESS scores .5, regardless of specialization group, indicating that increased time in the sport did not improve their neuromuscular control according to the LESS. Gymnasts must be strong and exhibit sound body coordination to perform various techniques, but early sport specialization can lead to overdevelopment or underdevelopment of muscle groups due to repeated movement patterns.…”
Section: Discussionmentioning
confidence: 71%
“…28 Previous authors who evaluated landing patterns on the LESS in a youth athlete population showed that an average total LESS score ,5 was associated with a decreased risk of ACL injury 16 and that athletes who had been exposed to a variety of sport experiences had better movement techniques. 20 Gymnasts in this sample had average total LESS scores .5, regardless of specialization group, indicating that increased time in the sport did not improve their neuromuscular control according to the LESS. Gymnasts must be strong and exhibit sound body coordination to perform various techniques, but early sport specialization can lead to overdevelopment or underdevelopment of muscle groups due to repeated movement patterns.…”
Section: Discussionmentioning
confidence: 71%
“…Participants were then compared based on sport sampling status (high, moderate, and low) and single-sport and multi-sport specialization, while using the three-tier classification method to validate their specialization definition. 45 Athletes with a high sport sampling were more likely to be classified as having "good" jump-landing mechanics than moderate and low sport sampling athletes. 45 Multi-sport athletes were more likely to demonstrate "good" jump-landing mechanics compared to single-sport athletes in this population, but no differences were demonstrated between singlesport and multi-sport athletes when mean LESS score was evaluated as a continuous variable.…”
Section: Discussionmentioning
confidence: 91%
“…45 Athletes with a high sport sampling were more likely to be classified as having "good" jump-landing mechanics than moderate and low sport sampling athletes. 45 Multi-sport athletes were more likely to demonstrate "good" jump-landing mechanics compared to single-sport athletes in this population, but no differences were demonstrated between singlesport and multi-sport athletes when mean LESS score was evaluated as a continuous variable. 45 This study suggests that sport sampling has neuromuscular control benefits in the youth population.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations